ACCESS TO JUSTICE AND THE INSTITUTIONAL LIMITS OF INDEPENDENT COURTS - Micah B. Rankin (The Windsor Yearbook of Access to Justice, 2012)
Canadian citizens’ inability to access courts has been a subject of controversy for decades. Despite widespread evidence that Canada’s legal aid system is faltering, governments continue to be unwilling to commit the resources necessary to remedy the problem. In the meantime, Canadian courts have failed to develop constitutional standards defining the government’s obligations to ensure that Canadians have access to courts. In this paper, the author argues that people’s inability to access courts and obtain legal representation not only has implications for their rights and interests, but may also create specific burdens on courts and judges that can sometimes undermine their independence. The author argues that the traditional view of judicial independence is too narrow and should be expanded. Judicial independence, the author claims, is best understood as a variable bundle of rights, guarantees and powers conferred on courts and judges that preserves and enhances their abilities to adjudicate impartially, maintain a constitutional distribution of powers and uphold the rule of law. Since people’s inability to access courts and obtain legal representation can impair the judiciary’s ability to preserve these values, the author argues that judicial independence is undermined. Relying on his broadened conception of judicial independence, the author claims that it is possible to correct problems of inaccessibility by recognizing that courts have a power to appoint state-funded counsel in appropriate circumstances in order to preserve their independence.